IMPACT OF BRAND EXPERIENCE ON THE CUSTOMER'S INTENTION TO REPEAT PURCHASE: AN ANALYTICAL STUDY OF THE OPINIONS OF A SAMPLE OF CUSTOMERS OF ZAIN IRAQ IN AL-MUTHANNA GOVERNORATE - Muthanna Twfiq Abdul –Hassan; Ahmad Abdul-Ridha Enad (Scholar Express Journal, 2023)
The study aims Seeks to Diagnose the Effect of the brand experience with its dimensions (Emotional Experience, Behavioral Experience, Cognitive Experience, Sensory Experience) on the Customer's intention to repeat the purchase. Developing two main hypotheses, and several hypotheses branching from them, to measure the level of association and influence by analyzing the relationship between these variables. Customers of zain Iraq in al-muthanna governorate were selected in the field to study and test their hypotheses, the questionnaire form was adopted as a main tool in collecting data related to the field side of the study. The sample size was (286) customers from zain Iraq in al-muthanna governorate, using statistical programs such as (spss.v.27), and a set of conclusions were reached, the most important of which is that the brand experience has a correlation and a significant effect on the intention to repeat the purchase. The study concluded with a set of recommendations.
Keywords: Brand Experience; Repeat Purchase Intention